Correction – Exercice 3

Exercice 3

Déterminer les limites en $+\infty$ de :

  1. $u_n = \dfrac{n}{5} + 7 – \dfrac{3n}{n^2+4}$
    $\quad$
  2. $u_n = \dfrac{6n^2-3n+7}{n^2+n+1}$
    $\quad$
  3. $u_n = \sqrt{\dfrac{3n^2-1}{5n+4}}$
    $\quad$
  4. $u_n = n^2 \left(\sqrt{3-\dfrac{2}{n}}-\sqrt{3}\right)$
    $\quad$
  5. $u_n = \dfrac{3n-\sqrt{9n^2+1}}{\sqrt{n^2+5}}$

Correction

  1. $u_n = \dfrac{n}{5} + 7 – \dfrac{3n}{n^2\left(1+\dfrac{4}{n} \right)}$ $=\dfrac{n}{5} + 7 – \dfrac{3}{1+\dfrac{4}{n}}$.
    $\quad$
    Or $\lim\limits_{n \rightarrow +\infty} 1+\dfrac{4}{n} = 1$ donc $\lim\limits_{n \rightarrow +\infty} \dfrac{3}{1+\dfrac{4}{n}} = 3$.
    $\quad$
    Mais $\lim\limits_{n \rightarrow +\infty} \dfrac{n}{5} = +\infty$.
    $\quad$
    Par conséquent $\lim\limits_{n \rightarrow +\infty} u_n = +\infty$
    $\quad$
  2. $u_n=\dfrac{n^2\left(6-\dfrac{3}{n} + \dfrac{7}{n^2}\right)}{n^2\left(1 + \dfrac{1}{n} + \dfrac{1}{n^2}\right)}$ $ = \dfrac{6 – \dfrac{3}{n} +\dfrac{7}{n^2}}{1 + \dfrac{1}{n} + \dfrac{1}{n^2}}$.
    $\quad$
    Or $\lim\limits_{n \rightarrow +\infty} \dfrac{1}{n} = \lim\limits_{n \rightarrow +\infty} \dfrac{1}{n^2} = 0$
    $\quad$
    Par conséquent $\lim\limits_{n \rightarrow +\infty} 6 – \dfrac{3}{n} +\dfrac{7}{n^2} = 6$ et $\lim\limits_{n \rightarrow +\infty} 1 + \dfrac{1}{n} + \dfrac{1}{n^2} = 1$.
    $\quad$
    Finalement $\lim\limits_{n \rightarrow +\infty} v_n = 6$
    $\quad$
  3. $\dfrac{3n^2 – 1}{5n+4} = \dfrac{n^2\left(3-\dfrac{1}{n^2} \right)}{n\left(5 + \dfrac{4}{n}\right)}$ $ = \dfrac{n\left(3-\dfrac{1}{n^2}\right)}{5+\dfrac{4}{n}}$
    $\quad$
    Par conséquent $\lim\limits_{n \rightarrow +\infty} \dfrac{3n^2 – 1}{5n+4} = +\infty$.
    $\quad$
    On a donc $\lim\limits_{n \rightarrow +\infty} u_n = +\infty$
    $\quad$
  4. $\quad$
    $\begin{align} u_n &= n^2 \left(\sqrt{3-\dfrac{2}{n}}-\sqrt{3}\right) \times \dfrac{\sqrt{3-\dfrac{2}{n}}+\sqrt{3}}{\sqrt{3 -\dfrac{2}{n}}+\sqrt{3}} \\\\
    &= n^2 \dfrac{3~ – \dfrac{2}{n} – 3}{\sqrt{3 -\dfrac{2}{n}}+\sqrt{3}}\\\\
    &=n^2 \dfrac{-\dfrac{2}{n}}{\sqrt{3-\dfrac{2}{n}}+\sqrt{3}}\\\\
    &=\dfrac{-2n}{\sqrt{3-\dfrac{2}{n}}+\sqrt{3}}
    \end{align}$
    $\quad$
    Mais $\lim\limits_{n \rightarrow +\infty}3-\dfrac{2}{n} = 3$ donc $\lim\limits_{n \rightarrow +\infty} \sqrt{3-\dfrac{2}{n}}+\sqrt{3} = 2\sqrt{3}$
    $\quad$
    Par conséquent $\lim\limits_{n \rightarrow +\infty} u_n = -\infty$
    $\quad$
  5. $\quad$
    $\begin{align} u_n &= \dfrac{3n-\sqrt{9n^2+1}}{\sqrt{n^2+5}} \times \dfrac{3n+\sqrt{9n^2+1}}{3n+\sqrt{9n^2+1}} \\\\
    &=\dfrac{9n^2 – (9n^2+1)}{\sqrt{n^2+5} \times \left(3n+\sqrt{9n^2+1} \right)} \\\\
    &=\dfrac{-1}{\sqrt{n^2+5} \times \left(3n+\sqrt{9n^2+1} \right)}
    \end{align}$
    $\quad$
    Mais $\lim\limits_{n \rightarrow +\infty} \sqrt{n^2+5} = \lim\limits_{n \rightarrow +\infty} 3n = \lim\limits_{n \rightarrow +\infty} \sqrt{9n^2+1} = +\infty$
    $\quad$
    Par conséquent $\lim\limits_{n \rightarrow +\infty} u_n = 0$.